Intermediate financial accounting 2016 : part 1B : based on Philippine financial reporting standards (PFRSs) - Millan, Zeus Vernon B. (Baguio City : Bandolin Enterprise, 2016)
"Intermediate financial Accounting parts 1A, 1B, 2 and 3 cover all topics tested in Practical Accounting Parts 1 and 2, Government Accounting and Accounting for non-profit-entries, Cost Accounting Problems 2, as given in the CPA board exam. Collectively, all of the books cover all topics tested in Theory of Accounts. Each chapter thoroughly discusses the provisions in a related financial reporting standard. Each financial reporting standards has an equivalent chapter ( or group of chapters) in order to facilitate browsing through the contents of this book. This is followed by a chapter summary, review questions and problems for classroom purposes and review questions for the CPA board exam subject Theory of Accounts."
Includes appendix and references.
Keywords: Financial accounting